1981
DOI: 10.1111/j.1469-8137.1981.tb02322.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death and Cell Wall Papillae in the Resistance of Oak Species to Powdery Mildew Disease

Abstract: Summary A quantitative study was made of the infection processes of Microsphaera alphitoides, powdery mildew, on seedlings of three oak species, Quercus robur (leaves highly susceptible until mature), Q. cerris (moderately resistant) and Q. borealis (highly resistant), to determine the mechanisms underlying their different resistances to disease. Some inhibition of spore germination occurred on mature leaves of Q. robur, and on leaves of Q. cerris and Q. borealis, but the number of appressoria formed from germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Their composition seems to depend on the characteristic phenol metabolism of the plant species. The observations of Edwards & Ayres (1981) in Quercus leaves infected by Microsphaerea alphitoides could be interpreted in a similar way: in that case the staining methods mentioned above were negative for both papillae and xylem but safranin, ammoniacal basic fuchsin and aniline sulphate-methylene blue indicated the presence of lignin in unperforated papillae.…”
Section: Defence Reactions Of the Host Cellmentioning
confidence: 87%
See 1 more Smart Citation
“…Their composition seems to depend on the characteristic phenol metabolism of the plant species. The observations of Edwards & Ayres (1981) in Quercus leaves infected by Microsphaerea alphitoides could be interpreted in a similar way: in that case the staining methods mentioned above were negative for both papillae and xylem but safranin, ammoniacal basic fuchsin and aniline sulphate-methylene blue indicated the presence of lignin in unperforated papillae.…”
Section: Defence Reactions Of the Host Cellmentioning
confidence: 87%
“…Callose seems to be the most frequent constituent (Sherwood & Vance, 1976;Ride & Pearce, 1979;Pratt et al, 1984;Skou, 1985;Smart, Aist & Israel, 1986 a, fe). Autofluorescence (Heath & Stumpf, 1986;Parry & Carver, 1986) indicates the presence of phenolic compounds which may be either different from lignins (Aist & Israel, 1986;Smart et al, 1986 a) or similar to lignins (Sherwood & Vance, 1976;Ride & Pearce, 1979;Edwards & Ayres, 1981). They also may contain silicon (Kunoh & Ishizaki, 1976;Zeyen, Carver & Ahlstrand, 1983;Stumpf & Heath, 1985;Ebrahim-Nesbat, Heitefuss & Rohringer, 1986, polysaccharides (Aist, 1976;Ebrahim-Nesbat et al, 1986), cutin, chitin, suberin, gums and pectin (Aist, 1976) and proteins, in particular peroxidases (Edwards, 1970;Delon, 1974;Ebrahim-Nesbat et al, 1986;Esquerre-Tugaye et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…What we are looking for is rather an attribute of the full tree crown, consistent from year to year. It might be based on fine‐tuned recognition systems, but detailed investigations into the resistance response of several oak species to M. alphitoides reveal a rather limited response of Q. robur in terms of cell necrosis and structural cytological changes (Edwards & Ayres 1981). This, together with the quantitative, not qualitative susceptibility of oaks observed in our reciprocal transplants, seems to argue against the existence of any fine‐tuned resistance response.…”
Section: Discussionmentioning
confidence: 99%
“…In the hydrangea-powdery mildew pathosystem, initiation of secondary germ tubes is a sign of the successful penetration with formation of functional haustoria in epidermal cells and establishment of a parasitic relationship (Li et al 2009). Strong inhibition of secondary hyphae initiation from appressoria of Microsphaera alphitoides was also reported on resistant oak species (Edward and Ayres 1981). In a previous study (Li et al 2009), we reported that accumulation of callose, a major compound of papillae, under the primary appressoria of E. polygoni occurred two days earlier in the resistant cultivar 'Veitchii' as compared with the susceptible cultivar 'Nikko Blue' (Li et al 2009).…”
Section: Discussionmentioning
confidence: 55%
“…HR is referred to as prehaustorial resistance (Niks and Rubiales 2002) and is controlled by a single gene in the wheat-rust pathosystems (Ellingboe 1972). HR in a resistant oak species, Quercus cerris, almost completely inhibited the formation of the secondary hyphae of M. alphitoides (Edward and Ayres 1981). The results of present study suggested that HR was not a qualitative resistance mechanism that completely prevents fungal penetration and haustorium formation in bigleaf hydrangeas, but the quantitative increase of necrotic cells in 'Veitchii' may have made a significant contribution to the resistance components that restrict fungal growth and reproduction.…”
Section: Discussionmentioning
confidence: 99%